2021
DOI: 10.1097/adm.0000000000000926
|View full text |Cite
|
Sign up to set email alerts
|

Nudging Emergency Department-Initiated Addiction Treatment

Abstract: ObjectivesWhen initiated in the Emergency Department (ED), medication for addiction treatment (MAT) with buprenorphine improves outcomes, increases engagement in addiction treatment and decreases the use of inpatient addiction treatment services. Unfortunately, initiating MAT in the ED is not yet standard practice. We assessed the impact of the addition of a multipart behavioral science-based intervention to increase opioid use disorder (OUD)-related treatments prescribed in the ED.MethodsOur ED initiated a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Given that EMBED increased the proportion of physicians who initiated buprenorphine, EMBED could play a role in changing practice as part of a more comprehensive implementation strategy. For example, multiple recent studies have begun to explore strategies to change behavior, such as nudge interventions,545556 that as part of a more comprehensive strategy could guide clinicians to EMBED resources.…”
Section: Discussionmentioning
confidence: 99%
“…Given that EMBED increased the proportion of physicians who initiated buprenorphine, EMBED could play a role in changing practice as part of a more comprehensive implementation strategy. For example, multiple recent studies have begun to explore strategies to change behavior, such as nudge interventions,545556 that as part of a more comprehensive strategy could guide clinicians to EMBED resources.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the 11 studies did not report the setting as either urban or rural ( 42 , 45 , 52 ). Three articles reported that the participating EDs were connected with psychiatric crisis centres or psychiatric EDs ( 44 , 45 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the 11 studies did not report the type of participating hospital (48,50,52). Eight of the 11 articles were conducted in urban settings (43,44,(46)(47)(48)(49)(50)(51), with one reporting an additional rural site (49). Three of the 11 studies did not report the setting as either urban or rural (42, 45,52).…”
Section: Innovations For Substance-related and Addictive Disorder Pre...mentioning
confidence: 99%